2015
DOI: 10.5194/bgd-12-191-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging tropical peatlands in Indonesia using ground penetrating radar (GPR) and electrical resistivity imaging (ERI): implications for carbon stock estimates and peat soil characterization

Abstract: Abstract. Current estimates of carbon (C) storage in peatland systems worldwide indicate tropical peatlands comprise about 15% of the global peat carbon pool. Such estimates are uncertain due to data gaps regarding organic peat soil thickness and C content. Indonesian peatlands are considered the largest pool of tropical peat carbon (C), accounting for an estimated 65% of all tropical peat while being the largest source of carbon dioxide emissions from degrading peat worldwide, posing a major concern regarding… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 48 publications
1
27
0
1
Order By: Relevance
“…Ground‐based geophysical methods, such as ground penetrating radar and electrical resistivity imaging, have been shown to be highly effective in detecting peat thickness at high spatial resolution (Comas et al, ; Slater & Reeve, ; Warner et al, ). Unfortunately, most of the geophysical studies we examined do not report the surface elevation, and thus, we could not use them in this study to correlate peat thickness and surface topography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground‐based geophysical methods, such as ground penetrating radar and electrical resistivity imaging, have been shown to be highly effective in detecting peat thickness at high spatial resolution (Comas et al, ; Slater & Reeve, ; Warner et al, ). Unfortunately, most of the geophysical studies we examined do not report the surface elevation, and thus, we could not use them in this study to correlate peat thickness and surface topography.…”
Section: Methodsmentioning
confidence: 99%
“…However, even though past efforts have traditionally focused on the characterization of the surface morphology of peatlands, e.g., its topography and extent, the importance of the morphology of the peat bottom has been understudied. Previous studies have demonstrated the ability of certain ground‐based geophysical methods such as ground‐penetrating radar or electrical resistivity imaging to characterize the morphology of the peat/mineral‐soil interface (Slater & Reeve, ; Comas et al, ; Parsekian et al, ), and ultimately to use these measurements to infer carbon stocks in peatlands (Comas et al, ; McClellan et al, ). However, these measurements are typically limited by their scale of measurement since they require direct contact with the ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…; Ponziani, Slob and Ngan‐Tillard ; Comas et al . ; Walter et al . , ) more rapidly and at various spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several studies using GPR have investigated multiple aspects of C cycling in peatlands including the quantification and monitoring of biogenic gases in peatlands (mainly methane and carbon dioxide) in northern [ Comas et al ., , , ; Parsekian et al ., ; Strack and Mierau , ] and subtropical systems [ Comas and Wright , ; Wright and Comas , ]. The method has also been used to refine C stocks in peat soils both in northern peatlands [ Parsekian et al ., ] and tropical systems [ Comas et al ., ]. However, to our knowledge, GPR has never been used in tropical mountain peatlands or in other similar high‐altitude peatland systems throughout the world.…”
Section: Introductionmentioning
confidence: 99%